Pilgrimage as a Reproduction of Sacred Landscape in Finnish Karelia and the Russian Border Zone - Mantsinen, Teemu (Temenos - Nordic Journal of Comparative Religion, 2020)
This article examines how pilgrimages are constructed as a shared ritual of seeking sacred traces, thus creating and reproducing the sacred landscape. It studies an annual event with three connected Finnish Karelian Orthodox processions as a pilgrimage from an anthropological perspective. The event combines various motives, goals, and participants through a similar construction of the sacred landscape, with rituals of nding and creating the sacred in and for the landscape with personal experiences and stories of the imagined past. These processions, one of which crosses the border with modern Russia, attract participants motivated by both religious and heritage tourism. The article draws inspiration from Laura Stark’s notion of a ‘cult of traces’ and engages with pilgrimage studies and theories to offer an analysis of how various acts such as religious rituals, storytelling, and taking pictures are combined in the reproduction and reinvention of the imagined past and the creation of a marked meaningful present to construct and sustain a sacred landscape, thusforming a pilgrimage.